(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Polycystic ovarian syndrome (PCOS) is commonly associated with metabolic syndrome, including insulin resistance and obesity. This study compares the effects of Metformin alone versus Metformin plus Dapagliflozin on metabolic parameters in women with PCOS. Methods: A 12-week randomized controlled trial was conducted at Lady Willingdon Hospital, Lahore, involving 40 women with PCOS. Participants received either Metformin alone (Group A) or Metformin with Dapagliflozin (Group B). Weight, HbA1c, fasting glucose, insulin, and lipid profiles were assessed at baseline and after 12 weeks. Results: Group B showed significantly greater reductions in weight (−8.3 ± 1.1 kg vs. −2.9 ± 0.8 kg; p < 0.001) and HbA1c (−0.5% vs. −0.2%; p = 0.002). Improvements in glucose, insulin, LDL-C, HDL-C, and triglycerides were also more significant in Group B (p < 0.01). Conclusion: The combination of Metformin and Dapagliflozin was more effective than Metformin alone in improving metabolic outcomes in PCOS. It may be a promising strategy for managing metabolic syndrome in these patients.